Bhanupaka: A Green Process in the Preparation of an Indian Ayurvedic Medicine, Lauha Bhasma. (14th February 2013) - Krishnamachary, Balaji; Purushothaman, Arun K.; Pemiah, Brindha; Krishnaswamy, Sridharan; Krishnan, Uma Maheswari; Sethuraman, Swaminathan; Sekar, Rajan K.
Abstract : The use of lauha bhasma, a traditional Indian herbometallic preparation, is in vogue for centuries for the treatment of various ailments related to iron deficiency. The preparation of lauha bhasma requires strict adherence to time-consuming, well-practiced, multistage, and multistep procedures. One of the steps is the treatment of purified metallic ingredients with Triphala decoction (the aqueous extract of Indian gooseberry, Chebulic myrobalans, and Beleric myrobalans) in the presence of sunlight (Bhanupaka). The formation of metal complexes due to the reaction of the metallic ingredients with the constituents of Triphala decoction has been ascertained by FTIR spectroscopy and carbon, hydrogen, and nitrogen analyses. Our results demonstrate that Bhanupaka is an essential step in the preparation of lauha bhasma.